2015
DOI: 10.3109/0886022x.2015.1010940
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis of idiopathic nephrotic syndrome in children

Abstract: Background: To investigate the demographic, clinical and laboratory data of the children with idiopathic nephrotic syndrome (INS), and to determine prognostic factors that affect the clinical outcome of the patients. Methods: Medical charts of 372 patients diagnosed to have INS and followed up at least 5 years between January 1990 and December 2008 were evaluated, respectively. After initial demographic, clinical and laboratory findings of the patients were documented, therapeutic protocols, prognosis and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…However, studies from Taiwan, Turkey and Nigeria with larger sample sizes showed a lower prevalence rate (about 3%-4%) of CKD. (2,8,(15)(16)(17) Hypertension, AKI and microscopic haematuria were the features of SRNS, (16)(17)(18) as well as the predictive factors for progression to CKD. (2,8,11) However, in our cohort, those features did not differ between patients with SSNS and SRNS.…”
Section: Table I Simple Cox Regression Analysis Of Potential Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies from Taiwan, Turkey and Nigeria with larger sample sizes showed a lower prevalence rate (about 3%-4%) of CKD. (2,8,(15)(16)(17) Hypertension, AKI and microscopic haematuria were the features of SRNS, (16)(17)(18) as well as the predictive factors for progression to CKD. (2,8,11) However, in our cohort, those features did not differ between patients with SSNS and SRNS.…”
Section: Table I Simple Cox Regression Analysis Of Potential Factorsmentioning
confidence: 99%
“…These findings were in accordance with other cohorts from Thailand, (15) Japan (22) and Iran (23) when compared to less than 50% from Europe (10) and Turkey. (16) Banh et al have reported that INS among Asians has a better outcome when compared to the European populations. (24) This high response rate in Asian patients, when compared to Western data, was possibly due to the influence of ethnic and genetic differences.…”
Section: Table I Simple Cox Regression Analysis Of Potential Factorsmentioning
confidence: 99%
“…Histologically, most children have minimal change disease (MCD); initial sensitivity to corticosteroids is used as a prognostic tool [2, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, persistent proteinuria which is unresponsive to therapy is an important correlate of disease progression in lupus nephritis. Additionally, it is well known that patients with resistant nephrotic syndrome, such as focal segmental glomerulosclerosis (FSGS) are at significant increased risk of progression to CKD [38]. In the CKiD cohort, Wong et al reported that patients diagnosed with a glomerular disorder causing CKD had Up/c levels that were on average 140 % higher than those in patients with CKD of nonglomerular etiology [6].…”
Section: Proteinuria In Children With Glomerular Disordersmentioning
confidence: 98%